A revised embedded planning tool for intensive reading instruction - Wei, Yan; Lombardi, Allison; Simonsen, Brandi; Coyne, Michael; Faggella-Luby, Michael; Freeman, Jennifer; Kearns, Devin (Learning Disabilities: A Multidisciplinary Journal, 2017)
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/057-076-036-438-880, pop00180 tex.type: [object Object]
Keywords: dept.rdg; dept.sed

Coteaching in content area classrooms: Lessons and guiding questions for administrators - Sinclair, Anne C.; Bray, Laura E.; Wei, Yan; Clancy, Erin E.; Wexler, Jade; Kearns, Devin M.; Lemons, Christopher J. (NASSP Bulletin, 2018)
Secondary school administrators increasingly include students with disabilities in general education classrooms with coteaching models. Theoretically, coteaching enables two educators to attend to the learning needs of students with disabilities while exposing them to grade-level content area instruction. However, our study on teachers’ perceptions of coteaching found that teachers often viewed their schools’ leadership decisions as adversely affecting their ability coteach effectively. The purpose of this article is to provide administrators with an overview of common coteaching models, summarize findings from our study on teachers’ perceptions of how their schools’ leadership influenced their coteaching practices, and provide a set of guiding questions to consider when seeking to support coteaching. © 2018 SAGE Publications.
7 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/010-514-925-194-03X, pop00123 tex.type: [object Object]
Keywords: coteaching; dept.rdg; dept.sed; inclusion; instructional leadership; peer-reviewed; professional development

Reading comprehension and co-teaching practices in middle school English language arts classrooms - Wexler, Jade; Kearns, Devin M.; Lemons, Christopher J.; Mitchell, Marisa; Clancy, Erin; Davidson, Kimberly A.; Sinclair, Anne C.; Wei, Yan (Exceptional Children, 2018)
This study reports practices implemented in over 2,000 minutes by 16 middle school special education and general education co-teaching pairs in English language arts classes. We report the extent to which teachers integrated literacy activities that support reading comprehension, the co-teaching models used, and the frequency with which each teacher led instruction. We also report the types of grouping structures teachers used and the extent to which teachers interacted with students with disabilities. Finally, we report the types of text used. Observations revealed that more than half of time spent on literacy activities involved reading aloud or silently with no co-occurring literacy instruction that supports reading comprehension. Students with disabilities spent a majority of their time in whole-class instruction or working independently with little teacher interaction. Special education teachers spent most of their time supporting whole-class instruction led by the content-area teacher. Implications and directions for future research are provided.
37 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/016-264-196-907-683, pop00086 tex.type: [object Object]
Keywords: dept.rdg; dept.sed; peer-reviewed